Oxymatrine attenuates melanoma progression and metastasis through SORBS2-mediated suppression of M2 macrophage polarization - Li, Xin; Ou, Yanhua; Chen, Jinling; Xiong, Junlong; Xu, Fangwen; Hu, Yaqian; Chen, Yuhan; Bai, Kunran; Chen, Jingyi; Meng, Yong; He, Jun; Lai, Caiyong; et al. (Elsevier GmbH, 2026)
Background Melanoma is an aggressive malignancy characterized by a highly immunosuppressive tumor microenvironment (TME), in which tumor-associated macrophages (TAMs) play a key role. Although oxymatrine (OMT) has been shown to exert anticancer effects, its mechanism of action in melanoma, particularly its interaction with Sorbin and SH3 Domain-Containing Protein 2 (SORBS2), remains poorly understood. Purpose To elucidate the molecular mechanisms by which oxymatrine inhibits melanoma growth and metastasis, suppresses M2-like macrophage polarization, and remodels the TME. Methods Cell viability, cell migration, and apoptosis assays were used to assess the effects of oxymatrine on melanoma cells. RNA sequencing (RNA-seq) was performed to identify oxymatrine’s potential target. The candidate target, SORBS2, was validated through molecular docking and surface plasmon resonance (SPR) to confirm its binding to oxymatrine. Western blotting and qRT-PCR were additionally used to measure SORBS2 expression for further validation. SORBS2-overexpressing or SORBS2-knockout cells and macrophage-melanoma co-culture systems were used to explore oxymatrine’s effects on M2-like TAM polarization. Results Oxymatrine inhibited melanoma proliferation and migration while inducing apoptosis. In vivo , oxymatrine suppressed tumor growth and metastasis. Mechanistically, oxymatrine upregulated SORBS2 expression, suppressed M2-like macrophage polarization, reduced the secretion of TGF-β and IL-10, and enhanced antitumor immunity. SORBS2 overexpression mimicked oxymatrine’s effects: it inhibited M2-like macrophage polarization and reduced TGF-β and IL-10 secretion, and thereby reshaped the immunosuppressive TME to enhance antitumor immunity. Conclusion These findings suggest that oxymatrine exerts anti-melanoma effects potentially by upregulating SORBS2, which in turn inhibits M2-like polarization and remodels the TME. This SORBS2-mediated mechanism provides a novel strategy for melanoma immunotherapy.